1978
DOI: 10.1002/pssb.2220900226
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and time decay analysis of photoluminescence excited in the A band region in KCl:Pb

Abstract: The A band spectral region in KCI: Pb is studied from the point of view of the optical absorption spectra, photoluminescence (emission and excitation) spectra, and the luminescence lifetime measurements in the temperature range 15 to 320 K. The sensitive ITC technique is exploited as a parallel tool to monitor and check the solution state of the impurity in order to rule out the additional and unwanted complications arising from the presence of aggregates. As a consequence only very dilute (4 to 6 ppm) and que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The quenched KCl: Pb2+ system is characterized by three absorption bands, but we are interested in the so-called A absorption band (centred at 273 nm) which corresponds to the 'So -+ 3P, transition and produces an emission band peaking at 340 nm. The decay scheme of this band is rather complex [6]. However, at room temperature it consists of a unique time decay constant whose value is about 200 ns.…”
Section: + Cationmentioning
confidence: 98%
“…The quenched KCl: Pb2+ system is characterized by three absorption bands, but we are interested in the so-called A absorption band (centred at 273 nm) which corresponds to the 'So -+ 3P, transition and produces an emission band peaking at 340 nm. The decay scheme of this band is rather complex [6]. However, at room temperature it consists of a unique time decay constant whose value is about 200 ns.…”
Section: + Cationmentioning
confidence: 98%
“…In the case of the Pb 2+ centre, only the A T emission band has been observed (see e.g. [3,9,10,19]). Some investigators, however, have observed another emission band which has been believed to be attributable to the A X emission band, besides the A T emission band [11 to 14].…”
Section: Introductionmentioning
confidence: 97%
“…The quenched KC1:Pb2+ system is charac- terized by three absorption bands but we are interested in the so-called A absorption band (centred at 273 nm) which corresponds to the 'So -+ 3P, transition and produces an emission band peaking at 340 nm. The decay scheme of this band is rather complex [5], however at room temperature it consists of a unique time decay constant whose value is about 200 ns.…”
Section: Introductionmentioning
confidence: 99%